Pengaruh Human Capital dan Marketing Capability Terhadap Kinerja Keuangan Perusahaan dan Nilai Pasar Perusahaan di Sektor Perdagangan Besar Barang Produksi dan Perdagangan Eceran (Kapitalisasi Kecil) - Catherine Pritania Lukito; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examined the affect between human capital and marketing capability to financial performance of companies which measured by the profitability and the market value. The sample of the study consisted of trade sector of goods industry and retail trade company (included in the category) of small capitalization and listed in Indonesia Stock Exchange (IDX). Data were collected from the annual reports for the period of 2009-2014. The total number of observations were 70 firm year. The hypotheses tested by using Multiple Linear Regression. Human capital measured by calculating value added human capital component. Marketing capability measured by using marketing and R&D expenditures, while profitability measured by using Return on Assets. Market value of this study measured using market to book value. This study used company size and company age as control variables. The results of this study found that human capital and marketing capability were significantly influence financial performance and market value and company age is significantly associated with market value.